Measurement Models of M-Government Services for Abu Dhabi Government - Murshed Almeqbali, Salem Rashed; Kasim, Rozilah (International Journal of Sustainable Construction Engineering and Technology, 2020)
This paper presents a formulation and assessment of measurement models which was intended for the study M-Government services by using service quality and customer satisfaction for UAE government. The study was conducted amongst users of Abu Dhabi Police smart application. In this study seven measurement models were identified. Five of the models which are Tangible; Reliability; Responsiveness; Assurance; Empathy are under the cluster of service quality. The other two which are M-services and overall customer satisfaction. A total of 250 questionnaire sets were considered adequate in accordance with the simple random sampling methods used to determine the sample size. The collected data was used in Structural Equation Modeling-AMOS for establishing and analysis each of the measurement model. The results found that all the seven models has achieved all the stipulated fitness criteria for the measurement model. Hence with all the model achieved the fitness level, these models can be used to develop structural model amongst them.